Phylogeny, Divergence Time Estimation and Biogeography of the Genus Onnia (Basidiomycota, Hymenochaetaceae) - Zhao, Heng; Zhou, Meng; Liu, Xiao-Yong; Wu, Fang; Dai, Yu-Cheng (Frontiers in Microbiology, 2022)
Species of Onnia are important tree pathogens and play a crucial role in forest ecosystems. The species diversity and distribution of Onnia have been studied, however, its evolutionary history is poorly understood. In this study, we reconstructed the phylogeny of Onnia using internal transcribed spacers (ITS) and large subunit (LSU) rDNA sequence data. Molecular clock analyses developed the divergence times of Onnia based on a dataset (ITS + LSU rDNA + rpb1 + rpb2 + tef1α). Reconstruct Ancestral State in Phylogenies (RASP) was used to reconstruct the historical biogeography for the genus Onnia with a Dispersal Extinction Cladogenesis (DEC) model. Here, we provide a robust phylogeny of Onnia, with a description of a new species, Onnia himalayana from Yunnan Province, China. Molecular clock analyses suggested that the common ancestor of Onnia and Porodaedalea emerged in the Paleogene period with full support and a mean stem age of 56.9 Mya (95% highest posterior density of 35.9–81.6 Mya), and most species occurred in the Neogene period. Biogeographic studies suggest that Asia, especially in the Hengduan-Himalayan region, is probably the ancestral area. Five dispersals and two vicariances indicate that species of Onnia were rapidly diversified. Speciation occurred in the Old World and New World due to geographic separation. This study is the first inference of the divergence times, biogeography, and speciation of the genus Onnia.